MENGUNJUNGI MUSEUM SENI PURBA DI KALIMANTAN - Sugiyanto, Bambang (Naditira Widya, 2010)
Kalimantan is wellknown for its karst environment, which bear rock shelters and caves. Apparently, the karst environment in East Kalimantan provides important information on prehistoric human occupation, especially humans appreciation toward narure in the form of art. The art in Marang is illustrated on cave walls as rock paintings of hand imprints and other images. Such presentation may be comparable to a museum display, however, it present in situ data with more invaluable cultural and historical information. This article discusses the uniquensess of materializing humans sense of art on cave wall and their role as museum for the benefit of future generation.